Precision conservation meets precision agriculture: A case study from southern Ontario. (November 2018) - Capmourteres, Virginia; Adams, Justin; Berg, Aaron; Fraser, Evan; Swanton, Clarence; Anand, Madhur
Abstract: Meeting future food demands for 9 billion people in the next 30 years will require either agricultural expansion or intensification to increase production. However, agriculture is already a major driver of biodiversity loss, as well as freshwater withdrawals, nutrient inputs, and greenhouse gasses, among other pressing environmental issues. In this paper, we look for solutions to this production-conservation challenge at the subfield scale. We use precision agriculture yield data from three farms in Southern Ontario and convert them into "profit maps" that show which regions of a field have management costs that exceed the market value of the commodities produced. We analyse the profit of three farms over time and identify areas that consistently show low or negative profit and thus constitute a compelling case for taking these areas out of production. We find, for example, that up to 14% of farmland can result in money loss and even more than 50% of the land might still not meet minimum revenue expectations. Further, we assess the economic feasibility of conservation strategies on these set-aside lands and find that investing in environmental benefits (even minimally) can often times be inexpensive when compared with economic losses due to failed harvests. We argue that profit mapping can serve as a management tool for farmers that will allow them to identify optimal crop areas, optimize nutrient inputs, plan for ecological intensification, and avoid economic loss all while providing ecosystem services at the local scale. Highlights: Precision agriculture yield data are converted into profit maps. Profit maps let us identify set-aside areas that can be taken out of production. Conservation in set-aside lands can be more economically feasible than agriculture. This methodology can help farmers manage risk and contribute to ecosystem services.